The first anthropology classes at Jagiellonian University in Kraków - Gajda, Zdzisław (Anthropological Review, 1978)
The author presents development of authropology at Jagiellonian University during the period prior to foundation of first in the entire Poland chair of anthropology at this particular university (in 1856). Professor Baltasar Hacquet who introduced elements of anthropology into his zoology classes is mentioned together with Aloizy Estreicher who taught class „De generis humani varietate nativa” (1819 - 1833) and published a treatise on man's natural history in 1833.